2015
DOI: 10.1073/pnas.1512255112
|View full text |Cite|
|
Sign up to set email alerts
|

Holocentromeres inRhynchosporaare associated with genome-wide centromere-specific repeat arrays interspersed among euchromatin

Abstract: Holocentric chromosomes lack a primary constriction, in contrast to monocentrics. They form kinetochores distributed along almost the entire poleward surface of the chromatids, to which spindle fibers attach. No centromere-specific DNA sequence has been found for any holocentric organism studied so far. It was proposed that centromeric repeats, typical for many monocentric species, could not occur in holocentrics, most likely because of differences in the centromere organization. Here we show that the holokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
161
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(171 citation statements)
references
References 46 publications
(44 reference statements)
6
161
1
1
Order By: Relevance
“…The observed absence of positive selection on CenH3 in Luzula is in accordance with a recent finding in Luzula elegans which lacks centromeric repeats that would co-localize with kinetochore formation along an entire chromosome (Heckmann et al, 2013). In contrast, Marques et al (2015) have found a centromeric satellite repeat Tyba co-localized with kinetochore formation in holokinetic Rhynchospora pubera (Cyperaceae). The authors offer two explanations, either the preferential insertion of Tyba sequences into centromeric chromatin might have been facilitated by CenH3 itself or, alternatively, Tyba might define the preferential sites for CenH3 accumulation (Marques et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The observed absence of positive selection on CenH3 in Luzula is in accordance with a recent finding in Luzula elegans which lacks centromeric repeats that would co-localize with kinetochore formation along an entire chromosome (Heckmann et al, 2013). In contrast, Marques et al (2015) have found a centromeric satellite repeat Tyba co-localized with kinetochore formation in holokinetic Rhynchospora pubera (Cyperaceae). The authors offer two explanations, either the preferential insertion of Tyba sequences into centromeric chromatin might have been facilitated by CenH3 itself or, alternatively, Tyba might define the preferential sites for CenH3 accumulation (Marques et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Marques et al (2015) have found a centromeric satellite repeat Tyba co-localized with kinetochore formation in holokinetic Rhynchospora pubera (Cyperaceae). The authors offer two explanations, either the preferential insertion of Tyba sequences into centromeric chromatin might have been facilitated by CenH3 itself or, alternatively, Tyba might define the preferential sites for CenH3 accumulation (Marques et al, 2015). Analysis of selection on CenH3 in Rhynchospora could help to resolve this dilemma; positively selected CenH3 could support Tybadirected CenH3 accumulation in a centromere drive fashion, while absence of positive selection on CenH3 could suggest that CenH3 facilitated Tyba insertion.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In interphase, the holocentromeres dissociate and form multiple individual centromere units. During chromosome condensation toward mitotic metaphase, the centromeric units rejoin and form a linear distinct longitudinal centromere within a groove to ensure faithful chromosome segregation (Marques et al 2015).In contrast to mitotic chromosomes, where the (peri)centromeric histone marker H2AThr120ph is also organized in a linear manner, a dispersed distribution was found in meiotic chromosomes of R. pubera. In addition, multiple CENH3 patches enhanced at the poleward chromosome surface of highly condensed metaphase I bivalents were reported (Cabral et al 2014).…”
mentioning
confidence: 99%
“…During mitosis CENH3-containing nucleosomes join, forming a polycentromeric band along the chromosomes. 1 A fraction of histones are non-allelic variants whose incorporation in place of canonical histones can lead to dynamic changes in chromatin structure and functions. Frederic Berger (GMI, Vienna, Austria) presented the work of his group on the histone variant H2A.W in Arabidopsis.…”
Section: Microscopy Molecules and Modeling: Elucidating Nuclear Orgmentioning
confidence: 99%